The firefly letters : a suffragette's journey to Cuba - Engle, Margarita (New York : Henry Holt and Co., 2010)
Draws on little-known Cuban history to tell a stirring story in poetry. Based on the diaries and letters of Swedish suffragist Fredrika Bremer, who spent three months in Cuba in 1851, the story focuses on oppressed women, the privileged as well as the enslaved, in three alternating free-verse narratives.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Novels in verse; Women -- Suffrage -- Cuba -- Juvenile fiction; Novels in verse; Women -- Suffrage -- Cuba -- Fiction